Pengembangan Virtual Learning Lab Berbasis Cloud Networking untuk Pembelajaran Infrastruktur Jaringan Komputer - Zulkipli Zulkipli; M. Firdaus Isnain; Ekal Syahrian; M. Hilal Mumtaz Lutfie; Tomy Ariq; Herman Supriantono (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop a cloud-based Virtual Learning Lab concept as an alternative to a flexible, cost-effective, and easily accessible computer networking practice laboratory. The research is motivated by the limitations of physical laboratories, such as the high cost of equipment procurement, infrastructure maintenance, and the imbalance between laboratory capacity and the number of students. The research method uses a descriptive conceptual approach through literature studies and analysis of the needs of a cloud-based virtual laboratory system by examining network emulation technology, horizontal elasticity, and auto-scaling. The results of the study produce a virtual laboratory architecture design consisting of a front-end in the form of a user web portal and a back-end in the form of a cloud-based network emulation server. The system is designed to support access across devices and operating systems, provide flexible practicum modules, and manage resources according to user needs. In addition, the study also produces a security management framework through setting access policies, monitoring user activity, and evaluating system security. The research findings indicate that a cloud-based virtual laboratory can improve the accessibility of computer networking practice, support large-scale practicum implementation, and reduce operational costs through a pay-as-you-use scheme, although its implementation still requires technical readiness, security governance, and good curriculum integration.